Implementing A Scorecard Scale in a Service Company: Case of a Moroccan Service Company - Farissi, Aicha; Jordan, Yeno Wora Lee (International Journal of Supply Chain Management, 2024)
This article focuses on the implementation of a Balanced Scorecard in a service company, examining its potential impact on performance improvement. Delving into the theoretical foundations of business performance management and the Balanced Scorecard, the first part of the work provides a comprehensive understanding of its implementation approach. The practical section offers insights into the company's situation through a post- implementation SWOT analysis, shedding light on the tangible outcomes of adopting a Prospective Dashboard. This exploration contributes valuable perspectives to the ongoing discourse on management practices in the face of dynamic global challenges.